Stereolithography assisted controllable random lasing device for tunable threshold, linewidth, and wavelength - Gummaluri, Venkata Siva (2023)
Additive manufacturing provides flexibility in making structures according to specific geometry requirements. Advances in this technology, including sophisticated laser-based stereolithography (SLA) technique, have paved the way to fabricate structures with layer resolutions up to 25 μm. Although the feasibility of random lasing is shown in 3D-printed structures, a study on varying lasing properties using SLA printing technique with continuous wave laser pumping is not studied yet in depth. Herein, SLA is used to fabricate structures conducive for random lasing. Randomly distributed vertical cylindrical microchannels are fabricated on a 1 cm × 1 cm photoresin chip of thickness 2 mm. The geometry of structures makes it viable for liquid optical gain media to be injected into the cylindrical channels. The random lasing characteristics are demonstrated including threshold and linewidths. Tunability in peak lasing wavelength, required threshold, and minimum achievable linewidth are demonstrated by changing the diameter of the microchannels. Further, it is shown that by changing the hole diameter from 260 to 470 μm, a wavelength tunability of approximately 22 nm is achieved. This structure expects to significantly contribute for its use as an on-chip photonic sensor, wherein liquid analytes achieved can be injected and sensed using optical parameters, and for on-chip spectroscopy applications.